KAJIAN TEOLOGIS TERHADAP FENOMENA EXORCISME: Studi Kasus Kerasukan yang Terjadi di Kalangan Remaja Jemaat GMIM Imanuel Ranolambot Wilayah Kawangkoan Dua - Lumempouw, Praysidita Fiadolorosa; Tombeng, Ineke (Educatio Christi, 2023)
This research discusses a theological study of the phenomenon of exorcism: a case study of possession that occurred among teenagers from the GMIM Imanuel Ranolambot congregation in the Kawangkoan Dua area. This is research that aims to find out the phenomenon of exorcism, in this case a case study of possession that occurs among teenagers. This research uses descriptive methods and a qualitative approach with data collection techniques including observation, interviews and documentation. This research was conducted in Ranolambot Village, Minahasa, specifically at the GMIM Imanuel Ranolambot Congregation. The findings of this research were that the GMIM Immanuel Ranolambot congregation's belief values ​​were found which could be collaborated with knowledge about exorcism. It was also found that there were inconsistencies in the faith of the congregation and the people of Ranolambot Village.